Realist Evaluation of the “Abiye” Safe Motherhood Initiative in Nigeria: Unveiling the Black-Box of Program Implementation and Health System Strengthening - Oladimeji, Olawale J.; Fatusi, Adesegun O. (Frontiers in Health Services, 2022)
Introduction: Realist evaluation studies have spanned different aspects of medicine especially in the field of public health. However, very few of these studies explicitly detailed how program implementation triggered outcomes which could strengthen understanding of its effect on Health System Strengthening in specific settings. In Low Middle-Income Countries, Nigeria inclusive, there is a paucity of realist evaluation studies, despite the implementation of multiple intervention programs and projects in these countries. This paper is aimed at unveiling the black-box of program implementation and Health System Strengthening of the ‘Abiye’ Safe Motherhood Program in Ondo State, Nigeria. Specifically, it identified the role of contextual factors in the ‘Abiye’ program in Ondo State, determined the mechanisms that facilitated or constrained outcomes of the ‘Abiye’ program and developed Context Mechanism Outcome (CMO) Configuration from which a Middle Range Theory (MRT) can be framed. Methodology: This was a qualitative research structured along the realist domains (Context, Mechanism and Outcome). The Initial Program Theory was validated by the qualitative study, after which a new Middle Range Theory was developed. The study population comprised of key stakeholders, secondary stakeholders and primary stakeholders in the Abiye safe motherhood program. Data was collected through ten key informant interviews, twenty-eight In-depth interviews and six Focus group discussions sessions. Thematic analysis was used to analyse all the qualitative data collected, and seven themes with nineteen subthemes emerged in the study. Results: We identified 13 contextual factors under five principal areas with most of the factors playing enabling role, some playing inhibitory while very few played both roles. We elicited 8 mechanisms and some of these facilitated the outcomes while some constrained the outcomes of the program. Health system strengthening was a key feature of the outcome of the program. We developed 6 CMO Configurations and from them developed a Middle-Range Theory. Conclusion and policy implication: Realist evaluation is an iterative process that looks beyond the surface to generate evidence. By applying the realist approach, we generated pieces of evidence which can be adapted for policymaking in public health interventions in LMIC